Patterns and Practices of Self-Medication Among Students Enrolled at Mbarara University of Science and Technology in Uganda - Niwandinda F; Lukyamuzi EJ; Ainebyona C; Ssebunya VN; Murungi G; Atukunda EC (Dove Medical Press, 2020)
Faith Niwandinda, Edward John Lukyamuzi, Calvin Ainebyona, Veronica Nambi Ssebunya, Godwin Murungi, Esther C Atukunda Department of Pharmacy, Mbarara University of Science and Technology, Mbarara, UgandaCorrespondence: Edward John LukyamuziDepartment of Pharmacy, Mbarara University of Science and Technology, P.O. Box 1410, Mbarara, UgandaTel +256 774-555726Fax +256 48520782Email elukyamuzi@must.ac.ugPurpose: Self-medication is drug use without advice from a medical professional. Proper self-medication can reduce health expenses and physician waiting time. However, prescription or over-the-counter drugs are considered unsafe when used irrationally. Presumably, university students can make informed decisions regarding their lives. However, there are limited studies documenting self-medication in Ugandan universities. This study sought to document the prevalence, patterns and factors associated with self-medication among students enrolled at Mbarara University of Science and Technology (MUST).Patients and Methods: A descriptive cross-sectional study was done on 385 medical and non-medical students. Data were collected by interviewer-led semi-structured questionnaires and analyzed using the Statistical Package for Social Sciences (SPSS) version 20. The statistical significance was considered as p < 0.05 for both univariate and multivariate analyses.Results: This study showed a 63.5% prevalence of self-medication. Self-medication reasons were classifying illnesses as minor (33%), time-saving (15%), having old prescriptions (11%) and high consultation fees (9%). Not self-medicating reasons included risk of using wrong drugs (19%), insufficient knowledge (17%), fear of side effects (15%), wrong drug use (15%) and misdiagnosis (14%). Respondents accessed drugs from pharmacies (56%), friends/family (17%) or private clinics (15%). Headache relievers, pain relievers and antibiotics were most commonly self-medicated. In adjusted analysis, being female, existing allergies, and being in advanced years of study were associated with increased odds of self-medication. No statistically significant difference existed between medical and non-medical students regarding self-medication. Self-medication likelihood increased with a lack of access to medical services.Conclusion: There is a high rate of self-medication amongst female students, those in advanced years of study and those with existing allergies. Medical services access significantly reduced the chances of self-medication. Vital medical services need to be extended to the university students to receive information on medicines, diagnosis, prescription and treatment. More studies should evaluate the impact of a high rate of self-medication among these students.Keywords: over-the-counter drugs, irrationally, prescription, drugs